1997
DOI: 10.1007/s004240050313
|View full text |Cite
|
Sign up to set email alerts
|

Run-down of the cardiac Ca 2+ channel: characterization and restoration of channel activity by cytoplasmic factors

Abstract: Possible mechanisms for run-down in the Ca2+ channel, such as proteolysis or dephosphorylation of the channel, were examined in guinea-pig ventricular myocytes. The Ca2+ channel current, recorded in inside-out patches using a pipette solution containing 50 mM Ba2+ and 3 microM Bay K 8644, ran down with a mean survival time of 2.35 min. The survival time was not significantly affected by adenosine triphosphate (ATP) (3 mM), 1,2-bis(2-aminophenoxy)ethane-N,N,N', N'-tetraacetic acid (BAPTA) (2 mM), isoprenaline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…In control conditions (i.e. in the absence of pharmacological interventions) peak I Ca was not stable but slowly ran down (Table 1, Control), in accordance with the literature (Kameyama et al 1997).…”
Section: Spontaneous Run-down Of I Casupporting
confidence: 76%
“…In control conditions (i.e. in the absence of pharmacological interventions) peak I Ca was not stable but slowly ran down (Table 1, Control), in accordance with the literature (Kameyama et al 1997).…”
Section: Spontaneous Run-down Of I Casupporting
confidence: 76%
“…The stock solution of protease inhibitors (×1000 concentration, protease inhibitor cocktail) contained 10 mM benzamidine, 10 mg / ml iodoacetamide, 10 mM PMSF, 2 mg / ml aprotinin, 5 mg / ml leupeptin, and 0.5 mg / ml pepstatin A (3,8). The homogenate was centrifuged at 10,000 × g for 20 min and then at 100,000 × g for 30 min.…”
Section: Preparation Of Cytoplasmic Fractionsmentioning
confidence: 99%
“…Recent work also shows that phosphatidylinositol-4,5-bisphosphate (PIP 2 ) can stabilize the activity of P / Q-type Ca 2+ channels (5,6). Alternatively, we have reported that a cytoplasmic extract from cardiac tissue recovers the Ca 2+ channel activity from run-down (3,7,8), suggesting that run-down of the Ca 2+ channel activity may be due to the washout of certain cytoplasmic factors. Subsequently the cytoplasmic factors were identified as calpastatin, ATP, and a yet unidentified factor in a high molecular mass fraction (H fraction) obtained from gel filtration of the cardiac tissue (3,9,10).…”
Section: Introductionmentioning
confidence: 96%
“…Inclusion of ATP, the catalytic subunit of protein kinase A (PKAc), or other agents that promote phosphorylation has been shown to dramatically decrease, and in some cases reverse, the run-down of whole-cell currents [6,8,9,10]. At the single-channel level, PKAc has been reported to prevent the run-down of HVA channels in the GH 3 cell line [11] and in myocytes [12], although there is conflicting evidence that PKAc prolongs activity in myocytes longer than in control excisions [13]. Yatani et al [14] found that a mixture of compounds that activate G-proteins and promote phosphorylation is able to reverse the run-down of cardiac HVA single channels in excised patches.…”
Section: Introductionmentioning
confidence: 97%